In vitro mineral nutrition for improving growth and multiplication of stevia - Poothong, Sukalya; Khen, Thanh; Chumphukam, Orada (Agriculture and Natural Resources, 2018)
In vitro propagation is important for rapid multiplication of a wide range of nursery crops or medicinal plants, including stevia (Stevia rebaudiana Bertoni). The aim of this study was to investigate the effects of mineral salts on plant growth and development of stevia shoot cultures. Response surface methodologywas used to design experiments by varying three factors: nitrogen salts (NH4NO3 and KNO3), mesos salts (CaCl2, KH2PO4 and MgSO4) and minor elements (Zn-Mn-Cu-Co-Mo-B-I-EDTA-chelated iron). The concentrations of each factor were defined as relative concentrations compared to Murashige and Skoog (MS) concentrations (0.5-3.0 x MS). The effects were evaluated of these three factors on plant quality, multiplication, shoot length and leaf numbers. The minor elements were the most significant factors associated with shoot length and leaf numbers. Increasing minor elements above an MS level of 1x and decreasing nitrogen tended to increase shoot length significantly. Increasing minor elements and nitrogen up to 3 x MS and increasingmesos to 1.5x MS were required to improve leaf numbers. Two optimized media were compared to MS for growth characteristics, phenolics and antioxidant activity. One of the media was identified as significantly better than MS for growth, low phenolic production and low antioxidant response.